Managing sport social and cultural perspectives - Hassan, David; Lusted, Jim.; T&F eBooks (Milton Park, Abingdon, Oxon ; New York : Routledge, 2012)
"Contemporary sport is shaped by wider society. Anybody working in sport today must be aware of the broader social and cultural context within which sport operates if they are to be effective as managers or professionals. This is the first book written especially for sport management students to examine the wider social and cultural environment and to fully explain the key issues and practical implications for everyday sport management. Written by a team of leading international experts on sport management and sport in society, the book explores important topics such as: - Corporate social responsibility in sport - Race - Gender and sexuality - Sport and the media - Globalisation - Politics and policy - Social class, social capital and social exclusion. Each issue is examined from the perspective of the manager or practitioner in sport, and each chapter includes a range of useful features, such as case-studies and self-test questions, to encourage the reader to think critically about the role of sport in society and about their own professional practice. This is the first sports management textbook to be based on the assumption that a more socially aware manager is a more effective manager and it should be essential reading for all sport management students."
1. Managing organizational performance in sport / Ian O'Boyle -- 2. Urban space, culture and sports in the Middle East : a case study of Casablanca, Morocco / Nicole Matuska -- 3. The management of anti-doping : an ongoing challenge for sport / David Reid and Paul Kitchin -- 4. Sanctioned aggression or criminal sanction? : violence, contact sports and the law / Jack Anderson -- 5. Reviewing the role of UK central government in sports development / Spencer Harris -- 6. Selling race equality to sports organizations : challenges and limitations / Jim Lusted -- 7. Sport and disability : the Special Olympics Youth Unified Sports programme / Sandra Dowling ... [et. al.] -- 8. Pain and injury within sporting cultures of risk / Lara Killick, Todd Davenport and Jodi Baker -- 9. Sport labour migration : managing a twenty-first-century global workforce / Pete Schroeder and Chris Janssen -- 10. The challenges of managing sport in a divided society : football in Jordan / Dag Tuastad -- 11. Managing gender equity in sport / Sally Shaw -- 12. The role of sport management in the creation of social capital / Richard Tacon -- 13. The changing nature of sports volunteering : modernization, policy and practice / Jimmy O'Gorman -- 14. Sporting preferences in the Arab world : examining consumerism in the United Arab Emirates / Sean O'Connor and David Hassan -- 15. The methodology of mega-events : the culture of vanity and measuring real benefit / Kamilla Swart and Urmilla Bob -- 16. Corporate social responsibility in the sports industry / Michelle Brassell -- 17. The dark sides of sport governance / Dino Numerato, Simone Baglioni and H. Thomas R. Persson -- 18. The evolution of sport management in the twenty-first century / David Hassan.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Sports -- Management; Sports administration; Sports -- Sociological aspects; Electronic books